Human centered computing : second International Conference, HCC 2016, Colombo, Sri Lanka, January 7-9, 2016, Revised selected papers /: second International Conference, HCC 2016, Colombo, Sri Lanka, January 7-9, 2016, Revised selected papers. ([2016]) - Unknown
No abstract available